Contribution of the private sector healthcare service providers to malaria diagnosis in a prevention of re-introduction setting. (December 2016) - Fernando, Sumadhya; Dharmawardana, Priyani; Epasinghe, Geethanee; Senanayake, Niroshana; Rodrigo, Chaturaka; Premaratne, Risintha; Wickremasinghe, Rajitha
Abstract Background Sri Lanka is currently in the prevention of re-introduction phase of malaria. The engagement of the private sector health care institutions in malaria surveillance is important. The purpose of the study was to determine the number of diagnostic tests carried out, the number of positive cases identified and the referral system for diagnosis in the private sector and to estimate the costs involved. Methods This prospective study of private sector laboratories within the Colombo District of Sri Lanka was carried out over a 6-month period in 2015. The management of registered private sector laboratories was contacted individually and the purpose of the study was explained. A reporting format was developed and introduced for monthly reporting. Results Forty-one laboratories were eligible to be included in the study and 28 participated by reporting data on a monthly basis. Excluding blood bank samples and routine testing for foreign employment, malaria diagnostic tests were carried out on 973 individuals during the 6-month period and nine malaria cases were identified. In 2015, a total of 36 malaria cases were reported from Sri Lanka. Of these, 24 (67 %) were diagnosed in the Colombo District and 50 % of them were diagnosed in private hospitals. Conclusions An equal number of cases were diagnosed from the private sector and government sector in the Colombo District in 2015. The private sector being a major contributor in the detection of imported malaria cases in the country should be actively engaged in the national malaria surveillance system.